Entrepreneurship competence among students and employees: A comparative study in five European countries - Venesaar, U.; Antonelli. G.; Dorożyński. T; Duarte, H.; Kallaste, M; Riviezzo, A.; Räisänen, M.; Santos, S. C. (Annals of entrepreneurship education and pedagogy: 2023, 2022)
To successfully transition from university to the labour market, students in higher education are expected to improve knowledge, skills and other competencies that contribute to the development of human capital. However, higher education institutions educate students by focusing on disciplinary, academic and technical skills (e.g., engineering, IT, business) while other important employability skills like work readiness skills (Heijke et al., 2003) or soft skills (World Economic Forum, 2018) can be less developed. At the same time, owners of micro and small businesses typically focus their education on needed business and management skills with less time on formal entrepreneurship training. This constitutes a skills gap that has important implications for curriculum design aiming to bridge the distance between the learning (university) and application (workplace) settings (Jackson, 2013). It is asserted here that entrepreneurship competence1 is essential, relevant across disciplines and in all modern careers and professional paths. Entrepreneurship competence includes a comprehensive set of knowledge, skills and attitudes necessary for implementing ideas, developing an entrepreneurial mindset, and sustainable coping with work and everyday life (Venesaar et al., 2018).